2009
DOI: 10.1183/09031936.00100609
|View full text |Cite
|
Sign up to set email alerts
|

Dairy food, calcium and vitamin D intake in pregnancy, and wheeze and eczema in infants

Abstract: The present prospective study examined the association between maternal consumption of dairy products, calcium, and vitamin D during pregnancy and the risk of wheeze and eczema in the infants aged 16-24 months.Subjects were 763 Japanese mother-child pairs. Data on maternal intake during pregnancy were assessed with a diet history questionnaire. Symptoms of wheeze and eczema were based on criteria of the International Study of Asthma and Allergies in Childhood.Higher maternal intake of total dairy products, mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
198
6
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(222 citation statements)
references
References 30 publications
9
198
6
9
Order By: Relevance
“…Rather, we observed a potential unadjusted protective effect of maternal intake of dietary folate on the risk of eczema. In addition, we did not confirm the associations that have been reported between vitamin C (Litonjua et al, 2006), calcium (Miyake et al, 2010b) and iron (Shahen et al, 2004) and the risk of eczema. So far, no study has investigated the effect of maternal intake of antioxidants on the risk of rhinitis in the offspring.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Rather, we observed a potential unadjusted protective effect of maternal intake of dietary folate on the risk of eczema. In addition, we did not confirm the associations that have been reported between vitamin C (Litonjua et al, 2006), calcium (Miyake et al, 2010b) and iron (Shahen et al, 2004) and the risk of eczema. So far, no study has investigated the effect of maternal intake of antioxidants on the risk of rhinitis in the offspring.…”
Section: Discussioncontrasting
confidence: 55%
“…Some studies have reported a reduced risk of asthma and wheezing in the offspring with high maternal intake of vitamin E during pregnancy (Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010a), whereas no association was observed regarding eczema (Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Similar inconsistencies have been seen concerning maternal intake of zinc and the risk of allergic outcomes (Shahen et al, 2004;Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Umbilical cord selenium and iron has been associated with wheezing and eczema in children (Shahen et al, 2004).…”
Section: Introductionmentioning
confidence: 71%
“…Most of the cohort studies followed children from the same country and differences in local eating patterns may restrict the generalizability of the outcome data, for example one Japanese study compared low vs higher dairy food intake, but their highest quartile only consumed 280g of dairy product per day [68]. The scoring systems used to rate 'Mediterranean dietary patterns' varied [57,66] making direct comparisons difficult.…”
Section: Limitations Of This Reviewmentioning
confidence: 99%
“…Two studies compared maternal dietary patterns (healthy, western, traditional or processed) [62,75] and two compared consumption of total and individual dairy products [54,68] with childhood eczema at two to three years of age, and found no significant association. This was also the case for maternal intake of fruit and vegetables in both studies, except that green and yellow vegetables and citrus fruit showed protective associations against eczema in Miyake et al [69].…”
Section: Observational Studiesmentioning
confidence: 99%
“…81 Several birth cohorts evaluating 25(OH)D levels in the maternal diet or cord blood have suggested an increased risk in childhood asthma symptoms. [82][83][84] It is possible that low 25(OH)D may be driving some of the asthma risk among obese children. However, further investigation is greatly needed.…”
Section: Dietary Factorsmentioning
confidence: 99%